A miniature tension sensor to measure surgical suture tension of deformable musculoskeletal tissues during joint motion. (February 2014) - Kiriyama, Yoshimori; Matsumoto, Hideo; Toyama, Yoshiaki; Nagura, Takeo
The aim of this study was to develop a new suture tension sensor for musculoskeletal soft tissue that shows deformation or movements. The suture tension sensor was 10 mm in size, which was small enough to avoid conflicting with the adjacent sensor. Furthermore, the sensor had good linearity up to a tension of 50 N, which is equivalent to the breaking strength of a size 1 absorbable suture defined by the United States Pharmacopeia. The design and mechanism were analyzed using a finite element model prior to developing the actual sensor. Based on the analysis, adequate material was selected, and the output linearity was confirmed and compared with the simulated result. To evaluate practical application, the incision of the skin and capsule were sutured during simulated total knee arthroplasty. When conventional surgery and minimally invasive surgery were performed, suture tensions were compared. In minimally invasive surgery, the distal portion of the knee was dissected, and the proximal portion of the knee was dissected additionally in conventional surgery. In the skin suturing, the maximum tension was 4.4 N, and this tension was independent of the sensor location. In contrast, the sensor suturing the capsule in the distal portion had a tension of 4.4 N in minimally invasive surgery, while the proximal sensor had a tension of 44 N in conventional surgery. The suture tensions increased nonlinearly and were dependent on the knee flexion angle. Furthermore, the tension changes showed hysteresis. This miniature tension sensor may help establish the optimal suturing method with adequate tension to ensure wound healing and early recovery.